2023
DOI: 10.21203/rs.3.rs-2581237/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing the efficiency of capture methods for questing Hyalomma lusitanicum ticks (vector of Crimean-Congo hemorrhagic fever virus)

Abstract: Background Available methods to census exophilic tick populations have limitations in estimating true population size due to their inability to capture a high proportion of the actual tick population. We currently ignore the efficacy of these methods to capture questing Hyalomma spp. ticks, vectors of the Crimean-Congo hemorrhagic fever virus. To address the need to accurately estimate questing densities of Hyalomma spp. we designed a field experiment to test the efficacy of blanket dragging, blanket flagging,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
0
1
Order By: Relevance
“…The higher antibody prevalence most likely results from including cattle in the survey. Our results also contrast markedly with the high antibody prevalence (76%-87%) observed in red deer in western Andalusia (40). Previous studies of small domestic ruminants from Africa, Asia, and Europe showed a wide range of seroprevalence, 0.4%-74% among sheep and 2.1%-66% among goats (28).…”
Section: Discussioncontrasting
confidence: 99%
“…The higher antibody prevalence most likely results from including cattle in the survey. Our results also contrast markedly with the high antibody prevalence (76%-87%) observed in red deer in western Andalusia (40). Previous studies of small domestic ruminants from Africa, Asia, and Europe showed a wide range of seroprevalence, 0.4%-74% among sheep and 2.1%-66% among goats (28).…”
Section: Discussioncontrasting
confidence: 99%